Pengaruh Social Media Marketing, Perceived Quality Dan Online Customer Review Terhadap Minat Beli Parfum Local Brand Hmns Pada Pengguna Instagram Dan Twitter - Suci Niswatussolihah; Beby Karina Fawzeea Sembiring; Marhayanie Marhayanie; Setri Hiyanti Siregar (Pusat Riset dan Inovasi Nasional, 2023)
Perfume is a secondary need that is in great demand and is used by various groups, from children, teenagers, to adults. Indonesia has various local and foreign perfume brands. The large number of perfume brands makes perfume business people use online platforms to sell and market products so that they can be known to many people and sell well in the market. This makes perfume business players compete fiercely to attract customers' buying interest, because customers make blind purchases. This research aims to determine the influence of social media marketing, perceived quality, and online customer reviews on interest in buying local brand HMNS perfume among Instagram and Twitter users. This type of research is associative research and the type of data used is quantitative. The population in this research is HMNS Instagram and Twitter followers. The sample in this study consisted of 100 respondents with the criteria of being at least 15 years old, active social media users who follow HMNS Instagram and Twitter accounts, and have purchased HMNS perfume at least once. The sampling technique is purposive sampling. The analytical method used in this research is multiple linear regression analysis processed with SPSS 26 software. The research results show that social media marketing, perceived quality, and online customer reviews simultaneously have a positive and significant effect on buying interest. Partially, social media marketing, perceived quality, and online customer reviews have a positive and significant effect on purchasing interest. The variable that has the greatest influence on purchasing interest in the local HMNS perfume brand is perceived quality, which has the highest significance value in the partial test.